'Curiouser and curiouser!': a reconnaissance of my doctoral study as a 'teacher-researcher'. Issue 1 (2nd January 2022) - Mat Noor, Mohd Syafiq Aiman
ABSTRACT: Unlike conventional studies that highlight research gaps, in action research methodology, 'reconnaissance' has been emphasised as an essential process to enable action researchers to initiate their work. This reflective piece illustrates a reconnaissance of my doctoral study as a 'teacher-researcher'. I used two dimensions of reconnaissance – 'unintentional' and 'intentional' – to explore my beliefs and experiences in the early stage of my doctoral study, as well as literature related to my research interest: inquiry-based teaching and learning in the primary science classroom. The reconnaissance of my doctoral study begins with a chronological account of my practice as a teacher in Malaysia, starting with preliminary reflections on the challenges I have faced. These reflections are followed by a discussion of the three main thematic concerns of the reconnaissance phase that led to my research interest in inquiry-based teaching and learning. The thematic concerns that emerged led to the identification of the purpose and objectives of my doctoral study, as well as the main research question and two subsidiary research questions. Ultimately, this reflective piece offers an exemplar for future doctoral students on how to begin an action research study through a critical self-examination of the 'unintentional' and 'intentional' dimensions of reconnaissance.